PROBLEMS IN WRITING IN ENGLISH AMONG HIGH SCHOOL LEARNERS - Abdiganiyeva Go’zalxon Oxunjon qizi (The Conference Hub, 2025)
Writing serves as a means of communication that utilizes symbols to represent a language. It is regarded as a highly productive skill; various writers express their creative ideas and thoughts through written forms. Writing offers learners a multitude of opportunities to explore contemporary methods for articulating their ideas and thoughts in a foreign language (Rao, 2017). Proficiency in English language skills is equally important and interrelated in the context of language acquisition.
Keywords: productive skill, literacy, communicative activity, memory, sharpness, creativity, incidents, success, failures.